2016
DOI: 10.1074/jbc.m116.732909
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Plakin Domain of Plectin Reveals an Extended Rod-like Shape

Abstract: Plakins are large multi-domain proteins that interconnect cytoskeletal structures. Plectin is a prototypical plakin that tethers intermediate filaments to membrane-associated complexes. Most plakins contain a plakin domain formed by up to nine spectrin repeats (SR1-SR9) and an SH3 domain. The plakin domains of plectin and other plakins harbor binding sites for junctional proteins. We have combined x-ray crystallography with small angle x-ray scattering (SAXS) to elucidate the structure of the plakin domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 73 publications
(69 reference statements)
2
42
0
Order By: Relevance
“…In such a scenario, DSP would act directly as a mechanosensor. Interestingly, several disease-causing mutations cluster in this region and are potentially linked to structural destabilization (Ortega et al 2016). A central, a-helical domain of DSP forms coiled coils leading to homodimerization.…”
Section: Concluding Remarks Desmosomes As Mechanosensors?mentioning
confidence: 99%
See 1 more Smart Citation
“…In such a scenario, DSP would act directly as a mechanosensor. Interestingly, several disease-causing mutations cluster in this region and are potentially linked to structural destabilization (Ortega et al 2016). A central, a-helical domain of DSP forms coiled coils leading to homodimerization.…”
Section: Concluding Remarks Desmosomes As Mechanosensors?mentioning
confidence: 99%
“…Decoupling of the plakin domains suggests that the hinge region might be extended and strained in an initial step, before the amino-terminal spectrin repeats undergo force-induced conformational changes (Ortega et al 2016). Therefore, the plakin domain may work as a molecular shock absorber that dissipates elastic energy when cells are subjected to external forces (Ortega et al 2016). …”
Section: Concluding Remarks Desmosomes As Mechanosensors?mentioning
confidence: 99%
“…Consequently, they demonstrated that MACF1 interacts with the β-catenin destruction complex in the cell, binding directly to Axin using the MACF1-spectrin repeat 0 (SR0) domain. The SR0 domain is defined as the region between the MACF1 plakin domain and the first spectrin repeat [41]. They also illustrated that either knockdown of MACF1 or overexpression of the MACF1 deletion fragment of SR0 successfully inhibits Wnt/β-catenin signaling by preventing Axin translocation to the cell membrane (Figure 1B) [13].…”
Section: Cellular Signaling Associated With Macf1mentioning
confidence: 99%
“…The experimental curve is characteristic of a rod-like elongated structure [37]; the longest distance D max of ~185 Å is close to the one inferred from the model and can only result from four SMP domains aligning along their longest axis. Variation in the curvature/bend of the complex could explain the discrepancy between experimental and calculated and D max values (Fig.…”
Section: Resultsmentioning
confidence: 59%